The Crane Husband - Barnhill, Kelly Regan (New York : Tor, 2023)
"Award-winning author Kelly Barnhill brings her singular talents to The Crane Husband, a raw, powerful story of love, sacrifice, and family. "Mothers fly away like migrating birds. This is why farmers have daughters." A fifteen-year-old teenager is the backbone of her small Midwestern family, budgeting the household finances and raising her younger brother while her mother, a talented artist, weaves beautiful tapestries. For six years, it's been just the three of them-her mother has brought home guests at times, but none have ever stayed. Yet when her mother brings home a six-foot tall crane with a menacing air, the girl is powerless to prevent her mom letting the intruder into her heart, and her children's lives. Utterly enchanted and numb to his sharp edges, her mother abandons the world around her to weave the masterpiece the crane demands. In this stunning contemporary retelling of "The Crane Wife" by the Newbery Award-winning author of The Girl Who Drank the Moon, one fiercely pragmatic teen forced to grow up faster than was fair will do whatever it takes to protect her family-and change the story"--.
"A Tom Doherty Associates book."
new book 2023 summer.
Keywords: Teenagers; Man-woman relationships; Women artists; Novels